Pelatihan Internet of Things (IoT) di SMA Negeri 1 Donorojo dalam Rangka Program Kerja KKN UNISNU Jepara - Ahmad Faidlon; Putri Aulia Faradina (Jurnal Pengabdian Masyarakat, 2024)
In the Industrial Revolution 4.0 era began to enter the virtual realm through connectivity between humans, machines, and data spread in various places and known as the Internet of Things (IoT) where the technology is needed in the current era. Internet of Things (IoT) is a technology that connects physical devices, vehicles, household appliances, and various other items. The Community Service Method used is offline training. The results of this Community Service are 30 participants who participated in the training with initially there were only 4 participants who understood the concept and application of IoT to 29 participants with a percentage of 86.2%, followed by participants' interest in the IoT field from 3 participants to 28 participants with a percentage of 89.2%, and activeness in question and answer sessions and discussions from 5 participants to 30 participants with a percentage of 83.3%.